Cloridrato de amiodarona – estudo comparativo de metodologias de análise de matéria-prima - Chiappa, Ricardo (2004)
The purpose of the author of the present work was to study the differences among the methodologies found in the literature taking into account only the description in the official codes of the volumetric titulation in acquous means to the determination of amiodarone chloridrate. The objective was to determine this substance in other types of samples and develop them in order to allow their employment in the identification and quantitative determination of the substance in study, as well as to provide subsidies in the form of methods of analysis to be incorporated in the Brazilian Pharmacopoeia. All the methodologies were studied, modified and validated according to the international norms. The methods developed presented linearity, precision and accuracy. They also showed equivalence when submitted to statistics studies, by means of variance analysis, according to the proposed to be officialized by the Brazilian Pharmacopoeia.